Performance analysis of an integrated piezoelectric ZnO sensor for detection of head–disk contact - Yuan, Yanhui (2013)
Integrated capability for detection of head-disk contact is desired for magnetic sliders with near-contact flying height. At the same time, fabrication of added features should be compatible with the existing slider micromachining process which is highly specialized and cost sensitive. Aimed at meeting the two requirements, a novel sensor configuration is explored in the present study. The new sensor configuration consists of a piezoelectric zinc oxide (ZnO) thin-film sensor sandwiched in the magnetic slider on its trailing side. Coupled structural and piezoelectric finite-element analysis for a sensor-slider- suspension assembly was performed to investigate the dynamic sensing performance. Output voltages on the millivolt level were obtained under typical head-disk interactions. The 2nd in-plane bending mode of the slider was found to be the major contributor to the output voltage. Parametric study showed that a thicker ZnO layer generally generated a larger output, while the thickness of the slider overcoat only had minimal effect. Simulation results from harmonic and transient analyses demonstrated that the piezoelectric thin-film ZnO sensor is sufficiently sensitive for detection of head-disk contact.